The Epilithic Diatom Community as a Bioindicator of water quality Brangkal Subwatershed in the Mojokerto Area - Bayu Agung Prahardika; Widi Muhammad Lutsfi Dwi Styawan (UIN Sunan Gunung Djati Bandung, 2022)
Diatoms are widely used as bioindicators of water quality because of their short life cycle and sensitivity to changes of environmental conditions in waters. Â One type of diatom that is used as a bioindicator is an epilithic diatom.Â Epilithic diatoms are one of the diatom microalgae communities attached to rock, so they are difficult to be carried away by currents. This study aimed to determine the type, composition, abundance, diversity, and dominance of epilithic diatoms found in the waters of the Brangkal subwatershed, and to determine the quality of water in the Brangkal subwatershed based on the epilithic diatom tropic index. Epilithic diatom samples were taken from 4 stations in the Brangkal subwatershed, Mojokerto Regency at the beginning of the dry season (July-August). The analysis carried out includes abundance, diversity index, dominance index, and Diatom Trophic Index (TDI). Based on the results of the study, 17 genera of epilithic diatoms were found, with the highest abundance of epilithic diatoms, including Navicula, Cocconeis, Nitszchia, and Gomphonema. The diversity index of all stations was in the medium category, with a value between 1.206 to 1.882. The lowest dominance index at station 1 was 0.167 and the highest was at station 4 with 0.373. In addition, the observed water quality is based on the Diatom Trophic Index (TDI), stations 1 to 3 are in a good category, and stations 4 are in a bad category.Â